3-Hydroxybenzo[a]pyrene in the urine of smokers and non-smokers - Lafontaine, M.; Champmartin, C.; Simon, P.; Delsaut, P.; Funck-Brentano, C. (Toxicology letters, 2006)
The people studied were male volunteers without occupational and dietary exposure to PAH: 27 smokers (10 cigarettes or more) and 27 non-smokers matched for age and socio-professional category. For each person, all the 24 h voided urine samples were reassembled in a single sample. 1-Hydroxypyrene (1-OHPy) and 3-hydroxybenzo[a]pyrene (3-OHBaP) were then determined by automated column-switching high-performance liquid chromatography. Urinary 1-OHPy ranged from 0.041 to 0.530 μmol/molCreatinine (arithmetic mean 0.144, median 0.115) for smokers and from 0.01 to 0.148 μmol/molCreatinine (arithmetic mean 0.044, median 0.032) for non-smokers. These values are close to those of some other studies. Urinary 3-OHBaP ranged from <0.01 to 0.084 nmol/molCreatinine (arithmetic mean 0.030, median 0.023) for smokers and from <0.01 to 0.045 nmol/molCreatinine (arithmetic mean 0.014, median 0.011) for non-smokers. Considering more particularly the urinary 3-OHBaP values, the influence of smoking could be important among workers exposed to low levels of BaP (<100 ng/m 3) and the concentrations for smokers were equivalent to most of the preshift values of exposed workers. The dietary BaP intake was slightly lower than the BaP intake for an average smoker. From the present study, temporary basic reference levels may be proposed for urinary 3-OHBaP.